WHAT IS THE APPROPRIATE VALGANCICLOVIR DOSAGE IN CHILDREN WITH SOLID ORGAN TRANSPLANT? A PROSPECTIVE PHARMACOKINETIC STUDY. Issue 1 (14th December 2015) - Peled, Orit; Ashkenazi-Hoffnung, Liat; Rom, Eran; Bilavsky, Efraim; Bernfeld, Yael; Dorfman, Lev; Amir, Jacob; Brandriss, Nurit; Bar-Haim, Adina; Berkovitch, Matitiahu
Abstract : Valganciclovir (VGC) is extensively used for cytomegalovirus (CMV) infection treatment and prophylaxis after solid organ transplantation (SOT). VGC dosing is problematic in children. VGC has variable absorption and is renally excreted. AUC0-24 of 40–60 mcg·h/L is a predictive pharmacokinetic parameter of efficacy and safety. Dosing based on manufacturer recommendations is supra-therapeutic in most cases. A few published dosing algorithms result in AUC out of range. Objective: To prospectively validate a VGC administration dosing regimen and compare it to other dosing algorithms. Methods: Children after SOT at Schneider Children's Medical Center, the largest tertiary pediatric center in Israel, were prospectively studied, starting Dec 2014. The dosing regimen was derived from Seattle Children's Hospital guidelines; 14–16 mg/kg/dose. For impaired renal function, stratified dose reduction was used. Blood was withdrawn at steady state: 2, 5 and 10 hours post dosing. Drug level was analyzed by HPLC. Results: Nine children aged 52 (37–137) [median; (inter-quartile range)] months were studied. Four had renal and 5 had liver transplantation. VGL dose administered was 16.67 (16.42–17.72) mg/kg/dose. AUC was 20.56 (18.7–22.7) mcg·h/L. AUC was sub-therapeutic in 8 children. Manufacturer-recommended dose in our patients was suppose to be 43.5 (24.84–46.7) mg/kg/dose, significantly higher than in our study (p=0.004). Dosing based upon Asberg et al study ( Pediatr. Transplantation 2014;18:103) –25.5 (19.38–25.5) mg/kg/dose, was significantly higher than in our study (p=0.009). Conclusions: VGC dosing regimen in SOT children is still not clear. There are significant differences between dosing algorithms. More studies are needed. Recruitment of patients to our study continues.